Large wood budget and transport dynamics on a large river using radio telemetry. Issue 4 (31st August 2013) - Schenk, Edward R.; Moulin, Bertrand; Hupp, Cliff R.; Richter, Jean M.
ABSTRACT Despite the abundance of large wood (LW) river studies there is still a lack of understanding of LW transport dynamics on large low gradient rivers. This study used 290 radio frequency identification tagged (RFID) LW and 54 metal (aluminum) tagged LW, to quantify the percent of in‐channel LW that moves per year and what variables play a role in LW transport dynamics. Aluminum tags were installed and monitored on LW in‐transit during the rising limb of a flood, the mean distance traveled by those pieces during the week was 13.3 river kilometers (km) with a maximum distance of 72 km. RFID tagged LW moved a mean of 11.9 km/yr with a maximum observed at 101.1 km/yr. Approximately 41% of LW low on the bank moves per year. The high rate of transport and distance traveled is likely due to the lack of interaction between LW floating in the channel and the channel boundaries, caused primarily by the width of the channel relative to length of the LW. Approximately 80% of the RFID tags moved past a fixed reader during the highest 20% of river stage per year. LW transport and logjam dynamics are complicated at high flows as pieces form temporary jams that continually expand and contract. Unlike most other studies, key members that create a logjam were defined more by stability than jam size or channel/hydrologic conditions. Finally, using an existing geomorphic database for the river, and data from this study, we were able to develop a comprehensive LW budget showing that 5% of the in‐channel LW population turns over each year (input from mass wasting and fluvial erosion equals burial, decomposition, and export out of system) and another 16% of the population moving within the system. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.